PENGARUH SIKAP, CARA BERPIKIR, MOTIVASI, PEMAHAMAN KEWIRAUSAHAAN DAN MODAL USAHA TERHADAP MINAT BERWIRAUSAHA MAHASISWA (STUDI KASUS PADA MAHASISWA UNIVERSITAS AL-IRSYAD CILACAP) - Asharryadi Noegroho (Jurnal Humaniora & Sosial Sains, 2024)
The presence of entrepreneurship has a positive impact on economic growth and progress of a country, through job creation, increased productivity and optimization of resources. For this reason, Al-Irsyad Cilacap University students are always directed to take part in various entrepreneurship programs or government programs in the economic sector to foster students' interest in entrepreneurship. This research aims to assess the influence of attitudes, ways of thinking, motivation, understanding of entrepreneurship, business capital on students' interest in entrepreneurship at Al-Irsyad University, Cilacap. This research model uses a descriptive methodology with a quantitative method that focuses on the object of UNAIC students. In this research, a quantitative method was used with a collection method using a questionnaire. Apart from that, analyzing data uses the SPSS application, including when carrying out validity and reliability tests, classical assumption tests, hypothesis testing, multiple linear regression and coefficient of determination. The population that will be used as research subjects is 39 respondents. Respondents are students at Al-Irsyad University Cilacap. It is hoped that this research will produce several variables including attitudes, ways of thinking, ways of motivating, ways of understanding entrepreneurship, ways of viewing business capital, and can influence the interest of Al-Irsyad Cilacap University students in entrepreneurship.